2003
DOI: 10.1097/00004703-200306000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Temper Tantrums in Young Children: 2. Tantrum Duration and Temporal Organization

Abstract: This article completes the analysis of parental narratives of tantrums had by 335 children aged 18 to 60 months. Modal tantrum durations were 0.5 to 1 minute; 75% of the tantrums lasted 5 minutes or less. If the child stamped or dropped to the floor in the first 30 seconds, the tantrum was likely to be shorter and the likelihood of parental intervention less. A novel analysis of behavior probabilities that permitted grouping of tantrums of different durations converged with our previous statistically independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 12 publications
4
73
0
1
Order By: Relevance
“…As expected, child age was significantly related to level of challenging behavior, with the highest mean challenging behavior scores occurring at age 2 years. This finding is consistent with previous research on the development of clinical behavior problems (Campbell, 2002) and with research on typical behavioral development that has reported that 75% of children exhibit aggression and tantrums by age 2 years (Potegal, Kosorok, & Davidson, 2003). Gender differences found on the Challenging Behavior factor suggest that the average reported level of challenging behavior is higher for boys than it is for girls; these differences were largest in children ages 2, 4, and 5 years.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, child age was significantly related to level of challenging behavior, with the highest mean challenging behavior scores occurring at age 2 years. This finding is consistent with previous research on the development of clinical behavior problems (Campbell, 2002) and with research on typical behavioral development that has reported that 75% of children exhibit aggression and tantrums by age 2 years (Potegal, Kosorok, & Davidson, 2003). Gender differences found on the Challenging Behavior factor suggest that the average reported level of challenging behavior is higher for boys than it is for girls; these differences were largest in children ages 2, 4, and 5 years.…”
Section: Discussionsupporting
confidence: 90%
“…Temper tantrums that include crying, stomping, pushing, hitting, and kicking are common in 1-4-year-old children and range in frequency from 5 to 9 times per week with an average duration of 5-10 minutes (Potegal et al 2003). The intensity and number of tantrums tend to decrease with age, although typically developing children continue to outwardly display anger and frustration, behaviors that parents often label as tantrums.…”
Section: Anger Irritability and Aggression As Treatment Targets Of mentioning
confidence: 99%
“…However, it is within development norms for children up to age 3 or 4 to tantrum on the average of once per day (Potegal et al, 2003). In addition, tantrums are reported as occurring among 75% of 3-to 5-year-old children, with rates decreasing to 21% among nonclinical samples of 6-to 8-year-old children (Bhatia et al, 1990).…”
Section: Prevalencementioning
confidence: 89%
“…For the purpose of this study, noncompliance will be defined as refusal to initiate an appropriate response within five seconds following a viable, parental command . Similarly, tantrums broadly refer to a wide range of disruptive behaviors or emotional outbursts displayed by children in response to unmet needs or desires (Potegal, Kosorok, & Davidson, 2003 In contrast, the diagnostic criteria for conduct disorder (CD) are consistent with more severe behaviors displayed along the CPS spectrum. Specifically, CD consists of aggressive and antisocial behaviors that include violations of the rights of others or deviations from major age-appropriate norms.…”
Section: Definitionsmentioning
confidence: 99%